HUBUNGAN RIWAYAT PEMBERIAN ASI DAN DURASI PEMBERIAN ASI DENGAN KEJADIAN OBESITAS PADA ANAK SEKOLAH DASAR - Satyawati, Ayu Putri; Sidiartha, I Gusti Lanang (E-Jurnal Medika Udayana, 2015)
RELATIONSHIP BETWEEN HISTORY OF BREASTFEEDING AND DURATION OF BREASTFEEDING WITH INCIDENCE OF OBESITY IN ELEMENTARY STUDENT The rate of obesity in children globally increased, that caused by many factors such as genetic and environment. The purpose of this research was to discover the relationship between the history of breastfeeding with obesity in children. This study was descriptive analytic study with cross sectional approach. This study uses 128 samples. Obesity in children was determined using body mass index for age and obesity stated if measurement exceed ?95th percentile based on CDC 2000.Data were analyzed using chi-square test, estimated risk and logistic regression.This study found9 from 31 children that have exclusive breast-feeding for at least 6 months (29 %) were obese, and 34 from 97 children who did not receive exclusive breastfeeding (35.1 %) were obese.In terms of duration of breast feeding, 16 from 55 children who were breastfed more than 1 year (29.1 %) were obese. Twenty one of 60 children who were breastfed less than or equal to 1 year (35 %) were obese. Sixof 13 children who were not breastfed at all (46.2 %) were obese. Result of bivariate analysisis of history of breastfeeding found p value is 0.537, odd ratio (OR) 0.758, Confident Interval (CI) (0.314;1.829) and in term of duration of breastfeeding found p value was 0.479. This study couldn’t prove there was significant relationship between a history of breastfeeding and duration of breastfeeding with the incidence of obesity in elementary school children.
Keywords: elementary school children obesity; breastfeeding history; duration of breastfeeding